Determinants of Adoption of Improved Maize Varieties among Resource-Poor Households in Kano and Katsina States, Nigeria - S Umar; M W Musa; L Kamsang (Journal of Agricultural Extension, 2014)
The study examined the factors influencing the adoption of improved maize varieties introduced under the Katsina-Kano-Maradi Pilot Learning Site (KKMPLS) of the IITA Sudan Savannah Taskforce. Using stratified sampling technique 160 farmers spread across five farming communities within Katsina and Kano States Nigeria were randomly selected. Data obtained were analyzed using probit regression model. Eleven variables were hypothesized to influence the probability of farmers’ adoption of improved maize varieties out of which four were found to be significantly influencing adoption of improved maize varieties in the study area. Household size and marital status of the farmers were found to be significant at 5% each; however, the former was negative while the later was positively related to adoption. Adoption of improved maize varieties was positively influenced by both participation in promotional activities and educational level of household head at 1% and 10% levels of significance respectively. It is, therefore, recommended that participatory approach should be encouraged in disseminating improved agricultural technologies like this because, participation is the most important factor influencing adoption of improved maize technologies in the study area.